If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(3g + 2) + -3g = 3(5g + -4) * 2 Reorder the terms: 8(2 + 3g) + -3g = 3(5g + -4) * 2 (2 * 8 + 3g * 8) + -3g = 3(5g + -4) * 2 (16 + 24g) + -3g = 3(5g + -4) * 2 Combine like terms: 24g + -3g = 21g 16 + 21g = 3(5g + -4) * 2 Reorder the terms: 16 + 21g = 3(-4 + 5g) * 2 Reorder the terms for easier multiplication: 16 + 21g = 3 * 2(-4 + 5g) Multiply 3 * 2 16 + 21g = 6(-4 + 5g) 16 + 21g = (-4 * 6 + 5g * 6) 16 + 21g = (-24 + 30g) Solving 16 + 21g = -24 + 30g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-30g' to each side of the equation. 16 + 21g + -30g = -24 + 30g + -30g Combine like terms: 21g + -30g = -9g 16 + -9g = -24 + 30g + -30g Combine like terms: 30g + -30g = 0 16 + -9g = -24 + 0 16 + -9g = -24 Add '-16' to each side of the equation. 16 + -16 + -9g = -24 + -16 Combine like terms: 16 + -16 = 0 0 + -9g = -24 + -16 -9g = -24 + -16 Combine like terms: -24 + -16 = -40 -9g = -40 Divide each side by '-9'. g = 4.444444444 Simplifying g = 4.444444444
| -5u-u=12 | | 5+r=17 | | 9x-9=x+15 | | 4.3x=11 | | 2y+4.5=11.5 | | 7x-5=2x+19 | | 24+7=38 | | 11x+8x= | | 3(8+7x)=192 | | 9x^3-6x^2-6x+4= | | 12+3p=8p+2 | | 3-8(2x-1)=27 | | 7+13=1 | | (a-bi)(a+i)=0 | | 7x+5-2x+8= | | -9=u-6 | | 4a+6a+8b-5b= | | 3x+7=15-12x | | -3w-(-9)=12 | | P(t)=5t^2+12t+2 | | z/3.5=4 | | 47-11=36 | | 2(12.5-4x)+2x=11.5 | | 9-16y^2=0 | | 42/0.2 | | 5(7a-8)=-320 | | 12z=168 | | 2(12.5-4x)+2y=11.5 | | 4y+2.6y=36 | | 2x+7=x+7+x | | 3x-2sin(x)+7=0 | | (a-bi)(3+5i)=0 |